Comparative analysis of Gram's stain, PNA‐FISH and Sepsityper with MALDI‐TOF MS for the identification of yeast direct from positive blood cultures. Issue 10 (26th May 2014) - Gorton, Rebecca L.; Ramnarain, P.; Barker, K.; Stone, N.; Rattenbury, S.; McHugh, T. D.; Kibbler, C. C.
Summary Fungaemia diagnosis could be improved by reducing the time to identification of yeast from blood cultures. This study aimed to evaluate three rapid methods for the identification of yeast direct from blood cultures; Gram's stain analysis, the AdvanDX Peptide Nucleic Acid in Situ Hybridisation Yeast Traffic Light system (PNA‐FISH YTL) and Bruker Sepsityper alongside matrix‐assisted laser desorption ionisation time of flight mass spectrometry (MALDI‐TOF MS). Fifty blood cultures spiked with a known single yeast strain were analysed by blinded operators experienced in each method. Identifications were compared with MALDI‐TOF MS CHROMagar Candida culture and ITS rRNA sequence‐based identifications. On first attempt, success rates of 96% (48/50) and 76% (36/50) were achieved using PNA‐FISH YTL and Gram's stain respectively. MALDI‐TOF MS demonstrated a success rate of 56% (28/50) when applying manufacturer's species log score thresholds and 76% (38/50) using in‐house parameters, including lowering the species log score threshold to >1.5. In conclusion, PNA‐FISH YTL demonstrated a high success rate successfully identifying yeast commonly encountered in fungaemia. Sepsityper™ with MALDI‐TOF MS was accurate but increased sensitivity is required. Due to the misidentification of commonly encountered yeast Gram's stain analysis demonstrated limited utility in this setting.